Low temperature synthesis of sub-micrometer yttria-doped barium zirconate thin films by modified chemical solution deposition technique - Biswas, Mridula (2019)
Yttria-doped barium zirconate (BZY) electrolyte films with submicrometer thickness were prepared using a modified chemical solution deposition (CSD) technique at very low sintering temperature of 800°C without sintering aid. Pure perovskite BZY phase without barium carbonate associated with low calcination temperature was successfully obtained with no obvious barium (Ba) evaporation to deviate the stoichiometry composition. This cost effective and scalable method for BYZ, as compared to the other reported vacuum-based thin film deposition techniques such as pulsed laser deposition (PLD) or atomic layer deposition (ALD), is potentially applicable in the fabrication of high quality electrolyte for nano-thin film micro solid oxide fuel cells operating at temperature below 500°C.